Profil Klinis dan Luaran Syok Sepsis pada Pasien Anak yang Dirawat di PICU RSUP Dr. M. Djamil Padang - Yoga Gandha Prasetya; Indra Ihsan; Amirah Zatil Izzah (Fakultas Kedokteran, Universitas Andalas, 2021)
Background. Septic shock is a common pediatric emergency with a high mortality rate. Objective. The purpose of this study was to determine the clinical profile and outcome of septic shock in pediatric patients treated at PICU of DR. M. Djamil Padang State General Hospital. Method. This descriptive study used data from medical records, conducted in the Medical Record Department of DR. M. Djamil Padang State General Hospital. The target population was pediatric patients which was diagnosed with septic shock in PICU through 2015 - 2017. Samples were collected by the total sampling technique. Result. During the following study of ninety-one patients septic and forty-eight having septic shock. Children having septic shock were commonly under one year of age, female, low nutritional status, having central neuron system infection of Klebsiella sp, having less than two organ dysfunctions with clinical manifestations of Hyperthermia, Tachycardia, and Tachypnea. Hematological profile found that patients commonly had anemia, leukocytosis, thrombocytopenia, and normal I/T ratio. Shock septic outcomes were found high mortality rate, almost some patients use a ventilator, high inotropic usage, and length of stay in living patients compared to dead. Conclusion. The study concluded that prevalence Septic Shock pediatric still high with higher mortality and also morbidity